Suppressor cell induction in vitro. II. Cellular requirements of suppressor cell induction. - Feldmann, M; Kontiainen, S (1976)
The cellular requirements for the induction of antigen-specific suppressor cells (SC) in vitro were studied. Macrophage depletion, by either nylon wool or polystyrene columns or iron (and magnet) treatment or a combination of methods, did not diminish SC induction, in contrast to its effect on helper cell induction. The requirement for T-T interaction in SC induction using splenic T cells was studied by the use of adult thymectomy and anti-lymphocyte serum, which selectively deplete short-lived and recirculating T cells respectively. Since suppressor cell induction was markedly diminished, or abolished by either procedure, but reconstituted by mixing these 2 populations, it was concluded that there was T-T interaction in the development of SC, just as there is in the induction of other T cell reactions, such as the graft-versus-host response, the T killer cell response, the helper cell response and, tentatively, delayed hypersensitivity. By the use of double-chamber tissue culture flasks, with the 2 cell populations separated by a cell impermeable membrane, it was found that T-T interaction does not require cell contact and is thus mediated by factor(s). The direct precursor of antigen-specific suppressor cells is resistant to adult thymectomy but sensitive to anti-lymphocyte serum.